Relationship between prostate cancer screening, linkage to the health system and associated factors in older adults from Bogotá, Colombia: Secondary analysis of the SABE survey (2018)
Introduction Prostate cancer is a high prevalence disease in our male population. Early diagnosis is important in order to improve its prognosis. The aim of this article is to describe the factors associated with prostate cancer screening of older adults in Bogotá, Colombia. Materials and methods The study used data from the Bogotá 2012 Health, WellBeing, and Ageing (Salud, Bienestar y Envejecimiento [SABE]) survey, which included 736 men aged 60 years or older. The dependent variable used was self-reported prostate screening in the last 2 years. An analysis was performed to determine the between this variable and socio-demographic variables and comorbidities using multivariate analysis. Results There was a prevalence of prostate cancer of 3.15%, with 57.8% of the population having had at least one prostate examination. Those affiliated to a health insurance scheme were more likely to be screened than the uninsured with an OR: 8.81, 95% CI: 2.92-26.63, P less than .001, as those affiliated to subsidized social security health scheme OR: 3.70, 95% CI: 1.20-11.41, P =.023, respectively). Conclusion There is inequity in the opportunity of screening for prostate cancer according to the type of health insurance scheme. Early detection strategies must be strengthened in order to include the entire population. Further studies are needed to provide more information on this issue. © 2018, Sociedad Colombiana de Urología. Publicado por Thieme Revinter Publicações Ltda., Rio de Janeiro, Brazil.